(untitled) (Tokyo, 1935)
Tell us history of Japan 's shipping and history of Nippong Yushen Kaisha Shipping Company, since 1885-1935
Keywords: Nihon Yusen Kabushiki Kaisha,Nihon Yusen Kabushiki Kaisha; History,Lịch sử